Conjunto de datos de retención de semillas - Lipoma, María Lucrecia; Cuchietti, Anibal; Gorné, Lucas D.; Díaz, Sandra M. (Willey, 2020)
Detalle de las variables incluidas en el archivo Lipoma_etal_database_2019.txt